2014
DOI: 10.1017/s0031182014000596
|View full text |Cite
|
Sign up to set email alerts
|

The effect of glycosylation of antigens on the antibody responses againstEchinostoma caproni(Trematoda: Echinostomatidae)

Abstract: In the present study, we analyse the effect of glycosylation in Echinostoma caproni (Trematoda: Echinostomatidae) antigens in antibody responses against the parasite in experimentally infected mice. It has been previously demonstrated that the mouse is a host of high compatibility with E. caproni and develops elevated responses of IgG, IgG1, IgG3 and IgM as a consequence of the infection, though the role of glycans in these responses remains unknown. To this purpose, the responses generated in mice against non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…These results suggest that hemocyanin carbohydrates participate in the specific humoral response, which is mediated by B lymphocytes that recognize various antigens, including oligosaccharides (65, 66). Indeed, anti-glycan antibodies have been previously reported; for instance, infections by some glycosylated parasites, such as Schistosoma mansoni , Toxocara canis , and Hemonchus contortus , among others, efficiently induce anti-glycan IgM and IgG (66, 67). Actually, specific serum against CCH, FLH, and KLH shows a decreased reactivity against hemocyanins in the presence of soluble mannose and galactose.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that hemocyanin carbohydrates participate in the specific humoral response, which is mediated by B lymphocytes that recognize various antigens, including oligosaccharides (65, 66). Indeed, anti-glycan antibodies have been previously reported; for instance, infections by some glycosylated parasites, such as Schistosoma mansoni , Toxocara canis , and Hemonchus contortus , among others, efficiently induce anti-glycan IgM and IgG (66, 67). Actually, specific serum against CCH, FLH, and KLH shows a decreased reactivity against hemocyanins in the presence of soluble mannose and galactose.…”
Section: Discussionmentioning
confidence: 99%
“…Glycomic studies of other trematodes, such as Schistosoma mansoni [ 17 ] and Opisthorchis viverrini [ 18 ] and most recently Echinostoma caproni [ 19 , 20 ] have led to a deeper understanding of the structural and functional aspects of glycans in this class of helminths. The immunomodulatory properties of F .…”
Section: Introductionmentioning
confidence: 99%
“…Biotechnological advances are offering new systems to generate recombinant proteins in eukaryotic cells, which allow higher yields of purified proteins with their posttranslation modifications such as glycosylations and acylations [9396]. These biotechnological tools can be essential to obtain isolated molecules in their native and original form, a characteristic that is largely vital for glycoproteins and lipoproteins activity and antigenicity as previously demonstrated for helminth molecules in some publications [58, 97]. In recent years, many proteomic studies revealed the composition of peptides of soluble egg antigens (SEA), adult soluble worm antigen (SWA) preparation, cercariae, schistosomula tegument, and adult worm tegument [98106] which, altogether, represent a vast repertoire of potential proteins to be evaluated in combinations or isolated in order to find key immunomodulatory proteins within these different and complex molecular mixtures from schistosomes.…”
Section: Discussionmentioning
confidence: 99%